Diagnostic accuracy of salivary hemoglobin, lactate dehydrogenase and Interleukin-6 to determine chronic periodontitis and tooth loss in type 2 diabetics - Sunila Bukanakere Sangappa; Harsha Mysore Babu; Ravindra C Savadi; Ashwini Jithendra (Elsevier, 2024)
Background: Salivary Hemoglobin (SH) has emerged as the mainstay non-invasive and a practicable screening method for Chronic Periodontitis. Current research aims to comprehensively assess the diagnostic value of Salivary Hb (SH) in comparison with Salivary IL-6 (SIL-6) and levels of Salivary lactate dehydrogenase enzyme (SLDH) amongst Type II Diabetes subjects having Chronic Periodontitis (CP) and associated tooth loss. Materials and methods: In this cross-sectional comparative investigation, 240 individuals with at least 15 remaining teeth, ranging in age from 30 to 70, were chosen and Group I controls were defined as follows: healthy (HbA1c levels ≤6.4 %) with no CP; Group II included chronic periodontitis and non-T2DM (HbA1c ≤ 6.4 %); Group III included T2DM (HbA1c ≥ 6.5 %) and CP; and Group IV included T2DM (HbA1c ≥ 6.5 %) with periodontitis-related tooth loss. ELISA colorimetric assay was used to quantify the results using the unstimulated whole saliva of fasting participants. Tukey's post hoc test was used for statistical analysis following Analysis of Variance (ANOVA), and Sensitivity and Specificity were computed following the determination of the correlation coefficient. Results: One-way ANOVA comparing Biomarker levels across the four groups revealed a statistically significant difference (F = 68.013) (p = 0.0001). Tukey's multiple post hoc yielded a significant difference between groups with least mean average biomarker levels observed among the controls (Group1) and maximum with group IV. Diagnostic Accuracy to discriminate between CP in T2DM & Controls with SH surpassed that of SIL-6 & SLDH, Receiver operating characteristic (ROC) curve depicted an overall sensitivity of 67.62 %, specificity of 80 % and accuracy of 74 % in T2DM subjects with tooth loss for the identification and assessment of CP. Conclusion: Estimates of Salivary Hemoglobin can assume an important role in comparison to SIL-6 & SLDH in determining the degree of periodontitis, including tooth loss, and identifying elevated glycemic levels. Advanced detection and monitoring can be ensured by routine use in dental offices and general practice.